A comparison of cervical smear adequacy using either the cytobrush or the Ayre spatula: a practice audit - Don O'Mahony; Lech Banach; Ehi U. Igumbor (South African Family Practice)
Background: To obtain an adequate cervical (Papanicolaou) smear, the transformation zone, including the squamo-columnar junction, should be sampled as carcinoma develops preferentially in this transformation zone. The Ayre spatula has been widely used but is not very effective. Other sampling devices have been developed to improve efficiency, including the cytobrush. The purpose of this study was to compare the adequacy of cervical smears taken with the Ayre spatula as opposed to the cytobrush.